Decoding the mystery between hyperuricemia and atrial fibrillation: new causal links through mediating proteomics - Zhang, Meiwei; Shi, Lei; Qin, Cong; Peng, Mengling; Zhang, Zhiguo (Frontiers in Endocrinology, 2025)
BackgroundAtrial fibrillation (AF), the most common cardiac arrhythmia, is associated with high incidence and mortality rates. Recent studies have confirmed a close correlation between hyperuricemia and the onset of AF, though the mechanisms remain unclear. Consequently, this study employs Mendelian randomization based on proteomics and mediation analysis to investigate the potential mechanisms by which hyperuricemia induces AF.MethodsA two-step mediation MR analysis was conducted to determine whether plasma proteins mediate atrial fibrillation induced by serum urate. The Reactome database was subsequently utilized to analyze the list of significant mediating plasma proteins to identify enriched pathways.ResultsMediation Mendelian randomization analysis suggested that hyperuricemia may promote the development of atrial fibrillation (AF) through 17 plasma proteins, includeing hepatocyte nuclear factor 4-alpha (HNF4α), identified as key mediators. Subsequent enrichment analysis of these proteins revealed 9 metabolic or signaling pathways potentially involved in this pathological process. Central mediator proteins such as HNF4α appear to drive AF through metabolic and inflammatory pathways.ConclusionThere is a close correlation between hyperuricemia and the onset of atrial fibrillation.